2020
DOI: 10.3390/joitmc6040193
|View full text |Cite
|
Sign up to set email alerts
|

Interfirm Partnerships and Organizational Innovation: Study of SMEs in the Automotive Sector

Abstract: This study aims to analyze the influence that interfirm partnership motives can have on the implementation of organizational innovation activities. To achieve this aim, a quantitative cross-sectional research design was adopted, surveying owners-managers of small and medium-sized enterprises in the automotive sector. Based on the empirical evidence, the study concludes that the motives for partnership formation are related to organizational innovation activities, but only partially. Of the four main factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The rapid growth of the innovative product in the world illustrates the prospects of this direction on a global scale. At the same time, the current number of users of innovative products is incomparably low (Compagnucci and Spigarelli, 2018;Coron and Gilbert, 2020;Courtney and Powell, 2020;Franco and Haase, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rapid growth of the innovative product in the world illustrates the prospects of this direction on a global scale. At the same time, the current number of users of innovative products is incomparably low (Compagnucci and Spigarelli, 2018;Coron and Gilbert, 2020;Courtney and Powell, 2020;Franco and Haase, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2024) To deepen our understanding of inter-firm knowledge transfer in R&D relationships, it is imperative that we shift our research focus from solely examining the outcomes of collaborative efforts or the acquisition of new skills and capabilities, to taking a process-oriented perspective that explores the formation and evolution of such knowledge transfer (Francesco Galati and Barbara Bigliardi, 2019;Azeem M. et al, 2021). Previous studies have reported positive impacts of such organizational innovations on innovation capabilities and firm performance (Yoon et al,2017;Mário Franco and Heiko Haase, 2020). This paper was intended to investigate several factors of interfirm partnerships impacted on the implementation of organizational innovation for Indonesian Automotive…”
Section: Introductionmentioning
confidence: 99%
“…Micro, small, and medium enterprises (SMEs) certainly play an important role in supporting the economy in a better direction (Ochinanwata et al, 2021). In both developed and developing countries, it turns out that SMEs are the largest contributor to the formation or growth of the gross domestic population (GDP) and contribute the most to employment than large businesses, this shows the importance of SMEs for the country's economy (Franco & Haase, 2020). (Mutegi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%